2022
DOI: 10.1186/s12866-022-02697-6
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic virulence profiles and associations in Salmonella isolated from meat samples in wet markets and abattoirs of Metro Manila, Philippines

Abstract: Background Salmonella are pathogenic foodborne bacteria with complex pathogenicity from numerous virulence genes housed in Salmonella pathogenicity islands (SPIs), plasmids, and other gene cassettes. However, Salmonella virulence gene distributions and mechanisms remain unestablished. In the Philippines, studies mainly report Salmonella incidences and antimicrobial resistance, but little to none on virulence profiles, their associations to animal sources, collection sites and Salmonella serogro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
1
4
0
1
Order By: Relevance
“…The frequency of virulence genes varied significantly across the townships or locations of the outlets studied except for gene pefC . This finding reflects the types and serovars of the infecting Salmonella and the practices that could have been affected by the types of farms, types of chickens, and their distribution across the townships, similar to the findings of others (Mthembu et al, 2019; Pavon et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The frequency of virulence genes varied significantly across the townships or locations of the outlets studied except for gene pefC . This finding reflects the types and serovars of the infecting Salmonella and the practices that could have been affected by the types of farms, types of chickens, and their distribution across the townships, similar to the findings of others (Mthembu et al, 2019; Pavon et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…All the isolates were carriers of at least one virulence gene using assays (SPI, plasmids, flagellin, CS54 island, and fimbriae), while 114 (42.5%) possessed one or more of the seven (38.9%) of the 18 AMR genes detected, Kumar et al (2021), in a similar study conducted on 'pluck shops'-processed poultry in Trinidad and Tobago, reported that of the 46 Salmonella isolates recovered, all were positive for one or more of the detected 12 (92.3%) of the 13 virulence genes tested while only 4 (33.3%) of the 12 AMR genes tested were detected. Variable frequencies of virulence and AMR genes have been reported for Salmonella isolates recovered from samples from the 'wet markets' elsewhere by others (Long et al, 2022;Pavon et al, 2022;Siddiky et al, 2022). The differences in the frequencies of virulence and resistance genes across the 'wet market' outlets in several countries may reflect the sample size, prevalence of Salmonella, types of genes tested for, and the types and use of antimicrobial agents in the poultry industry.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The avrA gene, which encodes an effector protein, is primarily involved in the enteritis pathway [33] and was detected only in four of the test isolates of this study. In a similar observation, the avrA gene was found in 30%-80% of the Salmonella isolates from food and food animal environments [34][35][36]. Genetic rearrangements within the pathogenicity islands result in variations within SPIs.…”
Section: Discussionmentioning
confidence: 56%
“…DISCUSIÓN El 28.9 ± 4.5% (111/384) de cepas positivas a Salmonella enterica aislados en esta investigación difiere de lo reportado por Soriano (2020), quién utilizando la misma metodología de muestreo en el mismo lugar de estudio aisló solo 5.1 ± 2.2% (20/393) de cepas positivas en la canal externa e interna de El incremento en el número de muestras positivas en esta investigación sugiere como posibles causas: el faenamiento de animales infectados, el pobre manejo de la higiene, limpieza y desinfección del área de faenamiento, errores durante la etapa de evisceración y deficiencia de los programas de vigilancia y control que limiten la contaminación de las canales en los mercados de abasto. Sin embargo, el aislamiento de Salmonella enterica en órganos de cuyes aparentemente sanos y enfermos reportada por otros autores demuestra que existe mayor probabilidad de exposición a la infección previo al proceso de manufactura (Salvatierra et Se reconoce como principal nicho de la Salmonella al tracto intestinal, por lo que la fuente de contaminación de estas canales sería de tipo fecal, donde la eliminación de esta bacteria puede ser intermitente, esporádica o constante, producto de la relación de las diferentes cepas de Salmonella y los diferentes hospedadores que infectan (Andino y Hanning, 2015; Crump et al, 2015), mostrando amplias variaciones de prevalencias de serotipos en diferentes animales de consumo, ubicación, y otras variables externas al serovar de Salmonella en estudio (Pavon et al, 2022).…”
Section: Resultsunclassified